ANALISIS BRAND AWARENESS DAN PESAN MEDIA RESTO KLASIK NY. SUHARTI TERHADAP KEPUTUSAN PEMBELIAN OLEH GENERASI MILENIAL DI JAKARTA - Garda Ardianto, (2023)
ANALYZE BRAND AWARENESS AND MEDIA MESSAGES OF RESTO KLASIK NY. SUHARTI ON PURCHASING DECISIONS BY MILLENNIALS IN JAKARTA ABSTRACT Garda Ardianto The phenomenon that is happening in today's society is related to the millennial generation who prefer fast food (fast food) in modern restaurants rather than eating at traditional restaurants. This study aims to find out how much influence brand awareness and media messages on the classic restaurant Ayam Goreng Ny. Suharti on the millennial generation for purchasing decisions for these products. The theory in this study uses the theory of communication inoculation to explain how to maintain initial attitudes and beliefs on previous products consistently amid attempts at persuasion messages. The method used in this study is a positivistic paradigm with a correlational type of quantitative research. The population in this study amounted to 400 samples using probability sampling data collection techniques with simple random sampling. The results of this study show a value of Significant = 0.000 < 0.025, it is stated that brand awareness has a significant influence on purchasing decision making. The results of the Media Message variable are Significant value = 0.075 > 0.025 so that in making decisions here there is no significant influence between Media Messages on the purchase decision of Mrs. Suharti's Fried Chicken products. The R Square Determination Coefficient value of 0.263 means that in the study the purchase decision was influenced by brand awareness and media messages by 26.3%, while the remaining 73.7% was influenced by other variables that were not studied in this study. Keywords: Brand awareness, media messaging, fast food, purchase decision.